INNOVATION OF DEODORANT STICKS AND LOTIONS BASED ON BETEL NUT EXTRACT AS AN ANTIBACTERIAL PROBLEM OF BODY ODOR AGAINST STAPHYLOCOCCUS AUREUS BACTERIA - Tari, Yusnia; Sihombing, Elsa Anggriani; Maimum, Maimum; Efendi, M Rifqi; Pratiwi, Pupa Dwi; Yuliawati, Yuliawati; Haryani, Yeni (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2025)
Body odor is a common problem caused by the interaction between sweat and Staphylococcus aureus bacteria. Areca nut has potential as a pharmaceutical preparation because it contains secondary metabolite compounds such as alkaloids, flavonoids, tannins, saponins and polyphenols which have antibacterial properties. This research aims to extract areca nut seeds using the maceration method with 96% ethanol and formulate them into stick deodorant and lotion with a concentration of 5%. Physical properties tests were carried out to evaluate pH, homogeneity, spreadability, melting point and antibacterial activity. The research results showed that stick deodorant had a pH of 4.5, while lotion deodorant had a pH of 5.5. Both preparations showed good homogeneity without the presence of coarse particles. The spreadability of the lotion was recorded at 5.3 cm, increasing to 5.5 cm with the addition of a 50 gram load. The melting point of bar deodoran is around 80°C, and bar deodorant melts completely within 60 minutes at 100°C. Both types of deodorant showed a significant inhibition zone diameter against bacteria, namely 18.16 mm for lotion and 16.77 mm for stiks. Areca nut extract showed very strong antibacterial activity with an inhibition zone diameter of 20.14 mm.